Radon exposure and COVID-19 mortality in pre-vaccination period: What links might exist? - Jean François Coudert; Ekaterina Dadachova; Gilles Maignant; Stephanie Jonathan (PLoS ONE, 2025)
Radon, a naturally occurring radioactive gas known for its health risks, has recently gained attention for its potential protective role against COVID-19 mortality. This cross-sectional ecological study examined the relationship between indoor radon exposure and COVID-19 mortality rates across eight countries, including several European nations, the United States, and the State of Kerala, India, during the pre-vaccination period. The analyzed data on the subject were derived from recent scientific publications. The environmental aspect was represented by the variable “indoor radon concentration or probability of exceeding a radon concentration in indoor air,” depending on data availability. Using national radon surveys and COVID-19 mortality statistics, statistical analyses, including Spearman’s correlation and Kendall Tau, were conducted between March and December 2020. The findings revealed a consistent negative correlation between radon concentrations and COVID-19 mortality rates, indicating that higher radon concentrations were associated with lower mortality rates. Regions such as Finland and Sweden, where radon exposure was relatively high, experienced significantly lower mortality. With Sweden and Finland showing a mortality risk reduction factor of respectively 1,42 and 5,47 during the first wave compared to the UK where Radon levels are very low. Although the findings are not overwhelmingly strong, the data suggest that radon exposure may have a mitigating effect on COVID-19 mortality.